The Moderating Role of the Tendency to Blame Others in the Development of Perceived Addiction, Shame, and Depression in Pornography Users. Issue 3 (2nd October 2019) - Volk, Fred; Floyd, Christopher G.; Bohannon, Kathryn E.; Cole, Susan M.; McNichol, Katie M.; Schott, Emily A.; Williams, Zachary D. R.
Abstract: In an extension of previous research on pornography users and their disapproval of their own use, support was found for a moderated mediation model in which the relationship between moral disapproval of pornography and depression was mediated by perceived addiction and sexual shame. This indirect effect was moderated by the tendency to blame others. Results demonstrate a possible sequence in which those who morally disapprove of pornography are more likely to perceive themselves as addicted, which is associated with an increase in sexual shame and is ultimately associated with higher levels of depression. Further, findings suggest that a tendency to externalize one's transgressions onto others simultaneously exacerbates and attenuates the negative associations in these relationships.